Adrenal cavernous hemangioma: a rare incidental finding from a routine ultrasound assessment - Muslim, Aisyah Khaulah; Amjad, Nasser Muhammad; Abd Fuaat, Azliana; Hassan, Radhiana (IIUM Press, 2024)
Cavernous hemangioma of the adrenal gland is a very rare benign vascular tumour. Its rarity and non-specific presentation pose a challenge to the radiologists and surgeons in making the correct diagnosis. We report a case of adrenal cavernous hemangioma in a 76-years old gentleman, in which a large heterogeneous mass was incidentally found at his left hypochondriac region during a routine KUB and prostate ultrasound assessment for benign prostatic hyperplasia. A multiphasic CT study performed and revealed a large mass with a maximum diameter of 18 cm occupying the left suprarenal area. Considering the large size of the left suprarenal mass with mass effect to the surrounding structures, the patient undergone left adrenalectomy. His final histopathological diagnosis revealed a cavernous hemangioma. This case highlighted literature review and role of imaging in this extremely rare benign tumour as one of the differential diagnoses of an adrenal incidentaloma.